Optimizations of Pulsed Plated p and n‐type Bi2Te3‐Based Ternary Compounds by Annealing in Different Ambient Atmospheres. Issue 1 (1st August 2012) - Schumacher, Christian; Reinsberg, Klaus G.; Rostek, Raimar; Akinsinde, Lewis; Baessler, Svenja; Zastrow, Sebastian; Rampelberg, Geert; Woias, Peter; Detavernier, Christophe; Broekaert, José A. C.; Bachmann, Julien; Nielsch, Kornelius
Abstract This work presents a comprehensive study of the fabrication and optimization of electrodeposited p‐ and n‐type thermoelectric films. The films are deposited on Au and stainless steel substrates over a wide range of deposition potentials. The influence of the preparative parameters such as the composition of the electrolyte bath and the deposition potential are investigated. Furthermore, the p‐doped (BixSb1‐x)2Te3 and the n‐doped Bi2(TexSe1‐x)3 films are annealed for a period of about 1 h under helium and under tellurium atmosphere at 250 °C for 60h. Annealing in He already leads to significant improvements in the thermoelectric performance. Furthermore, due to the equilibrium conditions during the process, annealing in Te atmosphere leads to a strongly improved film composition, charge carrier density and mobility. The Seebeck coefficients increase to values up to +182 μV K−1 for p‐doped and–130 μV K−1 for n‐doped materials at room temperature. The power factors also exhibit improvements with 1320 μW m−1 K−2 and 820 μW m−1 K−2 for p‐doped and n‐doped films, respectively. Additionally, in‐situ XRD measurements performed during annealing of the films up to 600K under He atmosphere show stepwise improvements of the crystal structure leading to the improvements in thermoelectric parameters. The thermal conductivity is between 1.2 W m−1 K−1 and 1.0 W m−1 K−1.